Effect of Graphene Oxide–Modified Cobalt Nickel Phosphate on Flame Retardancy of Epoxy Resin - Kong, Qinghong; Zhang, Caijiao; Zheng, Guolin; Zhang, Manman; Zhou, Tao; Zhang, Junhao (Frontiers in Materials, 2020)
In order to effectively improve the flame retardancy of epoxy resin (EP), a novel graphene oxide-cobalt nickel phosphate (GO-NiCoPO3) is successfully synthesized. GO-NiCoPO3 nanoplates are incorporated into EP matrix for preparing EP/GO-NiCoPO3 nanocomposites. The results show that the LOI value of EP/4GO-NiCoPO3 nanocomposites is as high as 30.3%, and UL-94 can reach V-1 rating. The results of micro-combustion calorimeter (MCC) indicate that the THR and PHRR values of EP/8GO-NiCoPO3 nanocomposites are decreased by 41.9% and 23.8% compared with pure EP. This is mainly due to the synergistic barrier effect of GO and NiCoPO3, which together play their own advantages. Meanwhile, EP/GO-NiCoPO3 nanocomposites can form a dense char layer during the burning process, and improve the thermal stability of EP/GO-NiCoPO3 nanocomposites.